Efficiency of ground motion intensity measures with earthquake-induced earth dam deformations. Issue 1 (February 2021) - Armstrong, Richard; Kishida, Tadahiro; Park, DongSoon
In a seismic hazard analysis (SHA), the earthquake loading level should be predicted for one or more ground motion intensity measures (IMs) that are expected to relate well with the engineering demand parameters (EDPs) of the site. In this study, the goal was to determine the IMs that best relate to embankment dam deformations based on nonlinear deformation analysis (NDA) results of two embankment dams with a large suite of recorded ground motions. The measure utilized to determine the "best" IM was standard deviation in the engineering demand parameter (e.g., deformation) for a given IM, also termed "efficiency." Results of the study demonstrated that for the NDA model used, Arias intensity (AI) was found to be the most efficient predictor of embankment dam deformations. In terms of pseudo-spectral acceleration (PSA)-based IMs, the PSA at short periods and then in the general range of the natural period of the dams was seen to be the most efficient IM, but was in almost all cases not as efficient as AI.